Strategy to Improve Service Quality at SD AL Azhar Syifa Budi - Chandrayani Puspita; Hidayati Tetra; Rahmawati Rahmawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The competition in the education business in Samarinda is getting more intense day by day, this is indicated by the increasing number of private schools in Samarinda, so the right strategy is needed to win the competition. Many factors can affect business success in the service sector, one of which is crucial is the service quality factor. SD Al Azhar Syifa Budi Samarinda wants to measure the satisfaction of the guardians of the students with the services they have provided, so that they have information on what service factors are still considered unfavorable by the parents, and based on that information they will be able to develop strategies for improving the services that are expected will be able to increase student satisfaction. The survey was conducted on the parents of Al Azhar Elementary School Syifa Budi Samarinda, involving 125 respondents where the survey was conducted online, from 227 parents who received the online questionnaire link, there were 125 people who wanted to participate. The data collected were analyzed by means ofimportance-performance analysis (IPA). The results of data analysis showed that the level of satisfaction of the guardians of students was 84.05%, and from science it was known that there were several factors that urgently needed improvement, namely the teacher understood each student individually (E1) on the Empathy dimension, Learning was running according to the school curriculum (RL2), School have a good reputation (RL3), and the academic department is always ready and disciplined in providing services (RL4) on the Reliable dimension, Teachers and the academic department are quick to respond to student guardian complaints (RS3) on the Responsiveness dimension, Students have excellent academic and non-academic abilities good (TQ1), students have a disciplined attitude both at school and at home (TQ2), and students have good communication skills (TQ5) on the Transformative Quality variable